(untitled) (Indo-MathEdu Intellectuals Journal, 2024)
This study aims to determine the effectiveness of the use of learning videos on students’ initial reading skills at SDN 52 Kuranji. This study uses a quantitative approach with a type of quasi-experimental desgin research with a pretest posttest control group design model The samples in this study were taken using a random sampling technique consisting of two classes, namely class 1A with 22 students as the experimental class and class 1B with 21 students as the control class. The data collection technique of this study uses an oral initial reading test. Data analysis techniques used normality test using the shapiro wilk technique, homogeneity test and non-parametic test- Mann Whitney for hypothesis testing. The results of data analysis showed that in the experimental class, the average pretest and posttest scores were 50.90 and 77.18, while in the control class, the average pretest and posttest scores were 53.38 and 63.80. Testing this hypothesis was carried out with a significance level of 0.05. Based on the results of the processing, it is known that there is a significant difference between the two classes. Therefore, it can be concluded that the use of learning videos is effective on students’ initial reading skills at SDN 52 Kuranji